Konsep Keadilan dan Perdamaian Dalam Islam - Adityo Dapi Pratama; M. Thoriqul Haq; Fadil Zalfa Firmansyah; Wafi Hidayat; Wismanto Wismanto; Fitria Mayasari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The concepts of justice and peace in Islam are fundamental elements that underlie the social, political and moral structure in Islamic society. Justice (al-'Adl) in Islam includes not only legal or distributive justice, but also social and spiritual justice which demands a balance between individual rights and collective interests. This research aims to provide a deeper understanding of the importance of these two concepts in creating a harmonious and civilized society, as well as how Muslims can contribute to creating a better world. This research is descriptive-analytic in nature, namely describing and analyzing in depth how Islam views justice and peace based on available sources. Following are the research steps: Determine the main research theme (justice and peace), collect data sources, read and analyze relevant texts, identify Islamic principles related to justice and peace. These principles of justice are strengthened by the teachings of the Koran and Sunnah which emphasize the importance of equal treatment, eliminating injustice and fulfilling human rights. Peace (as-Salam) in Islam is not only interpreted as the absence of conflict, but as a state of harmony rooted in justice and a sense of social responsibility. This research can provide deeper insight into the concept of justice in Islam. Islam teaches that justice is not only applied in the context of human relationships with God, but also in relationships between humans. This research can examine how these principles of justice can be applied in various contexts of daily life, including government, economics and social relations.